Auditor Burnout: Anteseden dan Konsekuensi - Laras Fuji Utami; Fitri Yani Jalil (Faculty of Economics, Universitas Internasional Batam, 2021)
This study aims to examine the effect of role pressure (role ambiguity, role overload, role conflict) and job demand on burnout felt by the auditor and the impact caused by the auditor on the auditor's job outcomes (job performance, job satisfaction, turnover intention) and commitment professional auditor. This study used primary data through the distribution of questionnaires to auditors in Indonesia, both those who had obtained a Certified Public Accountant (CPA) and those who had not. The method of determining the sample used in this study was convenience sampling. The number of auditors sampled was 73 auditors. The analytical method to test the hypothesis used by researchers was using SmartPLS 3.0. The results of this study indicate that the role ambiguity is not significant negative effect on burnout, role overload is not significant positive effect on burnout, role conflict has a significant positive effect on burnout, job demand is not significantly positive effect on burnout, burnout has a significant negative effect on job performance, burnout has a negative effect significant to job satisfaction, burnout has a significant positive effect on the turnover intention, and burnout has a significant positive effect on professional commitment. Keyword: role stressor, job demand, burnout, job outcomes, professional commitment